Aleksandar Kadijević: Yugoslav architecture between the two world wars (1918-1941): Contexts of interpretations, University of Belgrade-Faculty of Philosophy, Belgrade, 2023 - Antešević Nebojša (Arhitektura i Urbanizam)
In the monograph Yugoslav architecture between the two world wars (1918-1941): contexts of interpretations, published at the end of 2023 and written by dr. Aleksandar Kadijević, Full Professor at the Faculty of Philosophy, University of Belgrade, presents and discusses important aspects of historiographical research and interpretation of interwar Yugoslav architecture, with a special focus on the characteristics of the period and the ideological level, as well as other specifi c architectural topics related to this period - competition practice, visual culture, the infl uence of Expressionism and the architecture of emigrants from Russia. Emphasising the methodological basis of the study of interwar Yugoslav architecture, the author not only outlines the layering of research contexts, but also points out the importance of terminological characterisation.